Measuring Nurses’ Ethical Competence in Clinical Care: A Systematic Literature Review - Nurfika Asmaningrum; Denny Rifki; Dodi Wijaya (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Ethical competence is a fundamental requirement in the nursing sector. Justice, autonomy, beneficence, and non-maleficence are among the ethical principles that nurses must incorporate into their daily jobs. This implies the urgency for accurately measuring nurses’ ethical competency. This systematic literature review aims to identify and evaluate the existing instruments for measuring nurses' ethical competence in clinical settings. Methods: The present study curated works obtained from Google Scholar, PubMed, Springer, Science Direct, and Sage Journal as the basis to conduct a systematic literature review aiming to identify and evaluate the existing instruments for measuring nurses' ethical competence in clinical settings. Result: Of 14 articles that satisfied the inclusion criteria, 12 different instruments were found to measure nurses' ethical competence. Conclusion: This research has identified different and varied questionnaires. These questionnaires can be used according to contextual properties, such as the patient's condition and the cultural background of the setting where this questionnaire is operationalized.